Incidencia del entrenamiento de la resistencia aeróbica en el rendimiento deportivo de los jugadores de fútbol de la segunda categoría del colegio Caoitán Edmundo Chiriboga en el periodo 2011-2012 - Barragán Segura, Anderson Israel (2013)
The research is based primarily on the influence of physical training in soccer practice, All training must be based on the principle of progression. Player is essential to warm a cold muscle under a strain is at great risk of injury. Therefore physical preparation proves crucial for efficient performance on the field of play, for this reason in this study we considered the following objectives: Identify what the incidence of physical resistance factors in the second the football performance Cap College category. Edmundo Chiriboga identify what kind of activities should be developed for achieving high strength and velocity spaces at certain times of the meetings, for which we evaluate the physical strength of the players are known physical factors influence performance soccer player, identifies practices that are developed for physical strengthening of the players, and finally applies a training plan to improve the physical condition of the players, which will prepare to face the intercollegiate championship .